Evaluating Resmetirom Eligibility Among Patients with MASH: Insights from the German Steatotic Liver Disease-Registry - Messer, Eva Katharina; Petroff, David; Schattenberg, Jörn; Zeuzem, Stefan; von der Ohe, Manfred; Ludwig, Leopold; Demir, Münevver; Buggisch, Peter; Stein, Kerstin; Serfert, Yvonne; Wedemeyer, Heiner; Berg, Thomas; Hofmann, Wolf P.; Geier, Andreas; Wiegand, Johannes (Zeitschrift für Gastroenterologie, 2025)
The THR-β agonist resmetirom is the first treatment approved for metabolic dysfunction-associated steatohepatitis (MASH) in the US so far. It can be prescribed given MASH and F2/F3-fibrosis (“at-risk MASH”).We analyzed how many patients qualify for resmetirom in a recently recruited Steatotic Liver Disease-cohort involving both tertiary and secondary care centers, the German SLD-Registry.Indication for resmetirom was assessed by three different approaches: (i) biopsy-proven MASH with F2/3 fibrosis and NAS-score ≥ 4; (ii) FibroScan-AST (FAST) score ≥ 0.67 and vibration controlled transient elastography (VCTE) < 15 kPa; (iii) US expert recommendations with VCTE 10–15 kPa and platelets ≥ 140×109/L or VCTE 8–15 kPa.1113 patients were recruited across 8 tertiary and 12 secondary care centers. NAS grading and staging were available for 180 cases (16%) with 179/180 conducted at tertiary care level. Of these, 61 (34%) qualified for resmetirom. FAST score without histologic assessment was available for 638 cases (57.3%), of which 612 (87%) were from tertiary and 26 (11%) from secondary care centers. Based on approach (ii), 41 (6%) of these individuals qualified for resmetirom compared to 117 (18.3%) using approach (iii). Combining approach (iii) with FAST ≥ 0.67 leads to 191 (30.0%) eligible patients. Using VCTE 8–15 kPa results in 182 (28.5%) eligible patients.Eligibility for resmetirom treatment depends on the available method used to identify “at-risk MASH”. Availability of VCTE was highest among different levels of care.
Keywords: MASLD; MASH; Resmetirom; SLD; non-invasive tests